Kerjasama Pemerintah Provinsi Sulawesi Selatan dan United Nations Children’s Fund (UNICEF) dalam Rencana Aksi Percepatan Pengurangan Jumlah Anak Tidak Sekolah di Sulawesi Selatan - Pratiwi, Putri Amalia (Universitas Bosowa, 2024)
The collaboration between the South Sulawesi Provincial Government and UNICEF in the action plan to accelerate the reduction in the number of out-of-school children is one of the efforts or forms of seriousness of the South Sulawesi government in responding to the issue of out-of-school children in South Sulawesi, with Bone and Takalar Districts as the first trial sites for this program. This study uses a qualitative research method that will describe this collaboration objectively. In addition, this study will be explained through the concept of international cooperation by analyzing the implementation of this collaboration based on aspects of the concept. Thus, it is explained that the action to accelerate the reduction in the number of dropouts in Bone and Takalar has not been optimal because it produces a fluctuating trend.